Teachers’ Experience about the Roles of Classroom Questioning Technique in English Language Teaching: A Narrative Inquiry - Tiwari, Hari Prasad (Academia Research Journal, 2023)
The present study aims to investigate secondary level English Language (EL) teachers' lived experiences regarding the role of Classroom Questioning (CQ) strategy in English Language Teaching (ELT). The participants of this narrative inquiry consisted of four EL teachers who have been teaching at four different secondary level community schools in Banke district. I employed convenience sampling to select the schools and purposive sampling to select the participants. The data was collected employing unstructured interview and each of the interviews were audio recorded using an audio recorder. The collected data were transcribed and the findings of the study were presented and analyzed employing the thematic technique of qualitative data analysis. The study's key findings showed that CQ is important for assisting new teachers in the initial stages of their teaching profession with creating interactive classrooms, evaluating students' level of proficiency, determining students’ language learning difficulties, directing the classroom, promoting critical thinking and fostering a democratic environment in the classroom. Based on the results, it is concluded that CQ is an undeniable aspect of classroom interaction and functions as a fundamental and effective for teaching EL.